USE OF DAILY COMMUNICATION STRATEGIES FOR BASIC-LEVEL JAPANESE LEARNERS - Masilva Raynox Mael; Hiroaki Kitano (Universitas Negeri Surabaya, 2023)
Communication strategy is very important in interacting and conversing in a foreign language with native speakers. This research discusses the communication strategies used by a beginner Japanese learner from Indonesia who directly lives in Japan to communicate with Japanese people in everyday life. The data was taken from recording conversations with native Japanese speakers for 3 months in daily conversations. The result is that by using these communication strategies, a Japanese language learner can carry out daily activities by minimizing misunderstandings. The use of fillers or aizuchi is the most used strategy in conversations with Japanese people. Keywords: Communication strategy, Japanese, basic level